Step
*
of Lemma
rv-line-circle-lemma
∀n:ℕ. ∀r:ℝ. ∀p,q:ℝ^n.
  (p ≠ q
  
⇒ (||p|| ≤ r)
  
⇒ let v = q - p in
         (r0 ≤ (((r(2) * p⋅v) * r(2) * p⋅v) - r(4) * ||v||^2 * (||p||^2 - r^2)))
         ∧ (||p + quadratic1(||v||^2;r(2) * p⋅v;||p||^2 - r^2)*v|| = r)
         ∧ (||p + quadratic2(||v||^2;r(2) * p⋅v;||p||^2 - r^2)*v|| = r))
BY
{ (Auto THEN Assert ⌜r0 ≤ (p⋅q - p^2 - ||q - p||^2 * (||p||^2 - r^2))⌝⋅) }
1
.....assertion..... 
1. n : ℕ
2. r : ℝ
3. p : ℝ^n
4. q : ℝ^n
5. p ≠ q
6. ||p|| ≤ r
⊢ r0 ≤ (p⋅q - p^2 - ||q - p||^2 * (||p||^2 - r^2))
2
1. n : ℕ
2. r : ℝ
3. p : ℝ^n
4. q : ℝ^n
5. p ≠ q
6. ||p|| ≤ r
7. r0 ≤ (p⋅q - p^2 - ||q - p||^2 * (||p||^2 - r^2))
⊢ let v = q - p in
      (r0 ≤ (((r(2) * p⋅v) * r(2) * p⋅v) - r(4) * ||v||^2 * (||p||^2 - r^2)))
      ∧ (||p + quadratic1(||v||^2;r(2) * p⋅v;||p||^2 - r^2)*v|| = r)
      ∧ (||p + quadratic2(||v||^2;r(2) * p⋅v;||p||^2 - r^2)*v|| = r)
Latex:
Latex:
\mforall{}n:\mBbbN{}.  \mforall{}r:\mBbbR{}.  \mforall{}p,q:\mBbbR{}\^{}n.
    (p  \mneq{}  q
    {}\mRightarrow{}  (||p||  \mleq{}  r)
    {}\mRightarrow{}  let  v  =  q  -  p  in
                  (r0  \mleq{}  (((r(2)  *  p\mcdot{}v)  *  r(2)  *  p\mcdot{}v)  -  r(4)  *  ||v||\^{}2  *  (||p||\^{}2  -  r\^{}2)))
                  \mwedge{}  (||p  +  quadratic1(||v||\^{}2;r(2)  *  p\mcdot{}v;||p||\^{}2  -  r\^{}2)*v||  =  r)
                  \mwedge{}  (||p  +  quadratic2(||v||\^{}2;r(2)  *  p\mcdot{}v;||p||\^{}2  -  r\^{}2)*v||  =  r))
By
Latex:
(Auto  THEN  Assert  \mkleeneopen{}r0  \mleq{}  (p\mcdot{}q  -  p\^{}2  -  ||q  -  p||\^{}2  *  (||p||\^{}2  -  r\^{}2))\mkleeneclose{}\mcdot{})
Home
Index